Linguistic and Extralinguistic Factors that Influence the Process of Formation of Students' Communicative Competence in the Framework of the Use of Authentic English-Language Tv Series. (Eurasian Research Bulletin, 2023)
The purpose of this article is to study linguistic and extra-linguistic factors that contribute to the formation of communicative competence with the help of authentic Englishlanguage TV series. In the literary analysis, sources on the topic of language learning using serials were considered, as well as factors affecting the effective language acquisition. Using a research methodology based on the analysis of a survey of English language students, as well as teaching methods using serials, results were obtained on the perception of serials as language learning tools and on the influence of factors such as vocabulary, pronunciation, grammar and the psychological state of students. The discussion showed the need to use authentic series in the process of language learning, as well as taking into account linguistic and extra-linguistic factors when choosing series and teaching methods for the effective formation of communicative competence